TINGKAT KEPUASAN KONSUMEN â€œMARKOBARâ€ DI KOTA MANADO - Aprillina Maritha Rosa Ginting; Ribka M. Kumaat; Yolanda P.I. Rori (AGRI-SOSIOEKONOMI, 2018)
This study aims to measure the Level of Costumer Satisfaction â€œMarkobarâ€ in Manado City viewed from aspects of product, price, place, promotion, and service. This research was conducted in May to July 2017. Using primary and secondary data with sampling technique sampling accidental and respondents as much as 30 people wuth measuring instrument used is Likert scale. Research result showed that consumer satisfaction level of â€œMarkobarâ€ in Manado City is 87,79 % with very satisfield intrepretation.